2012
DOI: 10.1027/0227-5910/a000150
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Suicide Victims Who Leave Notes and Those Who Do Not

Abstract: Our study showed that there are indeed differences between suicide victims who leave a note and those who do not. We also suggest some explanations for these differences, which could represent a valuable starting point for future research on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
4
11
0
Order By: Relevance
“…These findings are somewhat in accordance with those reported by Paraschakis et al. () who observed that suicide decedents who left a suicide note were less likely to have had a psychiatric hospitalization within 12 months of their death.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are somewhat in accordance with those reported by Paraschakis et al. () who observed that suicide decedents who left a suicide note were less likely to have had a psychiatric hospitalization within 12 months of their death.…”
Section: Discussionsupporting
confidence: 93%
“…Studies that included in their analyses psychiatric histories and psychiatric hospitalizations reported contradictory findings. Several international studies reported that suicide decedents who had known mental health issues such as mental disorder, history of self‐harm, or recent or prior psychiatric hospitalization were less likely to leave behind a note (Carpenter et al., ; Chia, Chia, & Tai, ; Demirel, Akar, Sayin, Candansayar, & Leenaars, ; Ho et al., ; Howard & Surtees, ; Kuwabara et al., ; Paraschakis et al., ; Salib et al., ; Wong, Yeung, Chan, Yip, & Tang, ). Stack and Rockett (), in their analysis of US data from the National Violent Death Reporting System, found that those with current mental health issues or depression were more likely to have left a suicide note (OR = 1.11 & OR = 1.22, respectively); however, those with current mental health treatment and alcohol abuse‐related problems (15% and 24%, respectively) were less likely to have left a note.…”
Section: Discussionmentioning
confidence: 99%
“…For those suicide bereaved who may have considerable questions into their loved one's motives and psychological disposition at the time of their death, the content of these notes may provide invaluable insight and comfort. Some have suggested that the content may provide clues, which lead to healing for those left behind (Ho, Yip, Chiu, & Halliday, ) and insight into their loved one's suffering (Paraschakis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 5,000 suicides in Japan, note writers were more likely to be female, live alone, and die by methods such as carbon monoxide, hanging, or sharp instruments, while non‐note writers had more physical illness and psychiatric disorders (Kuwabara et al., ). In another recent study of 253 suicide deaths over a 2‐year period in Greece, psychological autopsies determined that note writers (26.1% of the sample) were more likely to die by hanging or firearm and had less history of psychiatric illness or psychiatric hospitalization (Paraschakis et al., ).…”
mentioning
confidence: 99%
“…Other inconsistent findings included gender, psychiatric disorders, prior suicide attempts and suicide methods (Callanan and Davis, 2009). Paraschakis et al (2012) suggested that cultural differences could play a role in explaining the inconsistent and often contradictory findings of the characteristics of note writers and non-writers in various international studies. As suicide note writers comprise a significant proportion of those who end their own lives, at the very least the notes give us insights into this substantial sub-group.…”
Section: Introductionmentioning
confidence: 97%